Peningkatan Kapasitas Pramuwisata dengan Sosialisasi Travel & Airline Terminology di Tanjung Pinang - Imam Ozali; Charles An; Haris Haris (Jurnal Abdimas Transportasi & Logistik, 2021)
The role of the tour guide is very important and very much determines the success of the tourists who will visit. With a professional tour guide, tourists who visit will bring a good impression. A good guide is the one who usually guides and takes tourists to tourist objects by paying attention to charm, courtesy and honesty. For this reason, tourist visits feel at home or not apart from objects, but what is equally important is the role of tour guides. A tour guide is a person in charge of providing guidance, information and directions on attractions or dimensions. However, during the covid-19 epidemic, the world of tourism suffered a heavy blow where all tourism sectors were severely affected which in turn would affect the Tour Guide. Therefore, the tour guides are required to be more creative and innovative by contributing all their thoughts so that they can survive in the covid-19 epidemic situation. Tour guides cannot be separated from the world of Air Transportation, because in the Tanjung Pinang City Tour Guide Capacity Building, resource persons provide material about Travel & Airlines Terminology from the perspective of the world of tourism. Thus, it can increase the understanding of tour guides about the world of aviation, so as to be able to provide satisfying services to tourists.